2006
DOI: 10.1016/j.jcrs.2006.01.066
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of corneal sensitivity after laser-assisted subepithelial keratectomy

Abstract: Recovery of corneal sensitivity began 1 month after LASEK and was completed by 3 months in eyes treated for low-moderate myopia and at 6 months in eyes with high myopia. The depth of ablation during surgery affected the recovery of corneal sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
(19 reference statements)
1
4
1
Order By: Relevance
“…No difference in the rate of recovery of corneal sensitivity or subbasal nerve morphology was observed in this study of LASIK and LASEK; however, Wu et al 39 and Lee et al 22 report that LASIK caused greater reduction in corneal sensitivity and subbasal nerve fiber density, respectively, than LASEK. This disagreement may be due to different surgical approaches.…”
Section: Subbasal Nervescontrasting
confidence: 66%
“…No difference in the rate of recovery of corneal sensitivity or subbasal nerve morphology was observed in this study of LASIK and LASEK; however, Wu et al 39 and Lee et al 22 report that LASIK caused greater reduction in corneal sensitivity and subbasal nerve fiber density, respectively, than LASEK. This disagreement may be due to different surgical approaches.…”
Section: Subbasal Nervescontrasting
confidence: 66%
“…The optic zone treated was also similar between groups: 6.99 ± 0.46 mm in CCN group and 7.16 ± 0.44 mm in SH group ( p > 0.05). 24 Furthermore, average keratometry was 7.49 ± 0.24 mm in CCN group, 7.46 ± 0.27 mm in SH group, and there was no statistically significant difference between groups ( p > 0.05).…”
Section: Methodsmentioning
confidence: 78%
“…Some studies have rejected the relationship regarding the effect of ablation depth or amount of myopia refractive error before surgery on the recovery of corneal sensation in LASEK [12] . In contrast, some have reported the existence of this relation significantly [14] . Also, concerning similar studies on other types of refractive surgeries, various results have been mentioned in this field.…”
Section: Discussionmentioning
confidence: 87%
“…Few studies are available regarding the recovery of corneal sensation after the LASEK, and the results have been somewhat contradictory. For example, Hermann et al [12] reported this duration as 1mo, while Wu et al [14] and Horwath-Winter et al [15] reported it as 3mo. Although refractive surgeries damage corneal nerve fibers, understanding the effects of these surgeries on corneal sensitivity and its recovery time is crucial.…”
Section: Introductionmentioning
confidence: 99%